2022
DOI: 10.1021/acs.iecr.2c00715
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework as an Efficient Synergist for Intumescent Flame Retardants against Highly Flammable Polypropylene

Abstract: The intumescent flame retardant (IFR) technique has been considered as an alternative to halogen-based flame retardants for reducing the fire hazards of polymers, especially highly flammable polyolefins. However, the IFR technique possesses certain disadvantages, such as unsatisfactory flame retardant efficiency, high loading requirements, and toxic smoke release. In this study, zeolite imidazolate frameworks-8 (ZIF-8), a common type of metal−organic frameworks (MOFs), was incorporated into an IFR/polypropylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…43 The I D /I G value for FRV/POD/ FRPET (3:2:5) is the lowest between the ternary blended fibers, which is beneficial to form the more compact residual char. 44 The results are consistent with the characterization of the residual char morphology above.…”
Section: Residual Char Analysissupporting
confidence: 90%
“…43 The I D /I G value for FRV/POD/ FRPET (3:2:5) is the lowest between the ternary blended fibers, which is beneficial to form the more compact residual char. 44 The results are consistent with the characterization of the residual char morphology above.…”
Section: Residual Char Analysissupporting
confidence: 90%
“…To achieve the optimum flame retardant effect, thermal decomposition should occur close to the beginning of flame retardant degradation, with a subsequent release of flammable volatiles. Other than that, the shape and size of the fillers are also crucial factors to be considered [ 238 , 239 ]. Fillers’ particle size and the requirement for high addition levels to confer adequate flame retardancy are usually limiting their potential in intumescent flame retardant coatings, in terms of both processability and final physical properties [ 112 ].…”
Section: Flame Retardant Coating Formulations and Designs: The Implem...mentioning
confidence: 99%
“…From the previous studies, it has been found that during the combustion process, volatile products are generated and released into the gas phase, and the combustion behaviors are mainly influenced by the production effect of the resulting char and gas inflation toward fractured char. Therefore, improving the quality and mass of chars is critical to reducing the flammability of polymers. …”
Section: Introductionmentioning
confidence: 99%